1997
DOI: 10.1177/0032855597077003005
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Probation and Parole Officer Attitudes to Achieve Desired Outcomes

Abstract: Much has been written about officer role orientations in probation and parole and about principles of effective correctional intervention, but little research adequately reflects the importance of linking these two discussions. The present study on officer attitudes provides a first step toward making this link. An officer attitude survey was conducted with both regular and intensive supervision officers at two different program sites. Each site recently implemented a prototypical model of intensive supervisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 12 publications
2
49
1
1
Order By: Relevance
“…Additionally, if agencies wish to moderate officers' existing attitudes towards supervision, they may consider employing training sessions geared towards achieving attitudinal change. Fulton, Stichman, Travis, and Latessa (1997) found that training officers on the principles of effective intervention (see, e.g., Cullen & Gendreau, 2000) was associated with attitudes towards supervision that were more treatment oriented and less focused on control (see also Lurigio & Skogan, 1994, for an application of this idea to police officers). Regardless of agency objectives, the findings from this study suggest parole officers' attitudes may have an important influence on their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if agencies wish to moderate officers' existing attitudes towards supervision, they may consider employing training sessions geared towards achieving attitudinal change. Fulton, Stichman, Travis, and Latessa (1997) found that training officers on the principles of effective intervention (see, e.g., Cullen & Gendreau, 2000) was associated with attitudes towards supervision that were more treatment oriented and less focused on control (see also Lurigio & Skogan, 1994, for an application of this idea to police officers). Regardless of agency objectives, the findings from this study suggest parole officers' attitudes may have an important influence on their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that probation and parole officers had conflicting views of their roles (e.g., as either law enforcement officers or social workers) might give some insight into how they viewed the sanction continuum. Numerous studies indicated that many officers used a combination of the two roles to perform their jobs (see Fulton, Stichman, Travis, & Latessa, 1997;and Studt, 1978, for examples). Hardyman (1988) found that some officers rotate between the two roles, depending on the perceived character and behavior of the offender.…”
Section: Correctional Official Perceptions Of Intermediate Sanctionsmentioning
confidence: 99%
“…Under this new model, probation officers were expected to make sure that offenders were made accountable for their actions (Forst & Blomquist, 1992). To achieve this, probation officers had to incorporate more punitive methods as a mechanism for preventing juveniles from re-offending (Fulton, Stichman, Travis, & Latessa, 1997).…”
Section: Introductionmentioning
confidence: 99%